BOUND HYDROGENIC STATES IN A MAGNETIC FIELD: A FINITE-DIFFERENCE APPROACH - Bernardino de Souza, Gustavo Vanin [UNESP]; Bruno-Alfonso, Alexys [UNESP] (World Scientific Publ Co Pte Ltd, 2009)
A finite-difference scheme is used to calculate bound electronic states of an electron in a hydrogen atom subject to a magnetic field. The numerical results are in good agreement with exact results, in the absence of the magnetic field, and with a two-parameters variational calculation, when the magnetic field is applied.
Keywords: Finite-difference; hydrogen; magnetic field